2018
DOI: 10.1002/hep.30153
|View full text |Cite
|
Sign up to set email alerts
|

A Transforming Growth Factor‐β and H19 Signaling Axis in Tumor‐Initiating Hepatocytes That Regulates Hepatic Carcinogenesis

Abstract: Our findings disclose a novel TGF-β and H19 signaling axis via Sox2 in TICs that importantly regulates hepatocarcinogenesis. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 45 publications
3
57
0
Order By: Relevance
“…Zhang et al found that TICs deficient in Tgfbr2 form HCC, whereas TICs with intact Tgfbr2 have a reduced capability to form tumors in recipient mice, supporting a tumor‐suppressive role of Tgfbr2 . This study provides direct evidence of tumor‐suppressive effects of TGF‐β signaling within the cancer cells, rather than the tumor stroma or microenvironment.…”
supporting
confidence: 56%
See 4 more Smart Citations
“…Zhang et al found that TICs deficient in Tgfbr2 form HCC, whereas TICs with intact Tgfbr2 have a reduced capability to form tumors in recipient mice, supporting a tumor‐suppressive role of Tgfbr2 . This study provides direct evidence of tumor‐suppressive effects of TGF‐β signaling within the cancer cells, rather than the tumor stroma or microenvironment.…”
supporting
confidence: 56%
“…Development of HCC is associated with alterations in the transforming growth factor beta (TGF-β) signaling pathway, which plays a critical role in cell proliferation, apoptosis, differentiation, motility, lineage specificity, as well as normal stem cell homeostasis. (1)(2)(3)(4) Mediated by TGF-β ligands that activate TGF-β receptors (TGFBR1 and TGFBR2) to stimulate downstream mothers against decapentaplegic (SMAD) proteins (SMAD2/3/4), the TGF-β signaling pathway positively or negatively regulates transcription of various gene targets involved in diverse biological functions. In addition, many other proteins-including the SMAD3 adaptor spectrin beta, nonerythrocytic 1 (SPTBN1); the TGFBRassociated protein Smad anchor for receptor activation; and the SMAD corepressors SNO/SKI-function as positive or negative regulators of TGF-β signaling.…”
Section: See Article On Page 1549mentioning
confidence: 99%
See 3 more Smart Citations